Defense and Adaptation: The Complex Inter-Relationship between Campylobacter jejuni and Mucus - Alemka, Abofu; Corcionivoschi, Nicolae; Bourke, Billy (Frontiers in Cellular and Infection Microbiology, 2012)
Mucus colonization is the first step towards the establishment of infection and disease by mucosal pathogens. There is an emerging literature implicating specific mucin subtypes and mucin modifications in protecting the host from Campylobacter jejuni infection. However, mucosal pathogens have evolved sophisticated mechanisms to breach the mucus layer and C. jejuni in particular appears to harbor specific adaptations to better colonize intestinal mucus. For example, components of mucus are chemotactic for C. jejuni and the rheological properties of mucus promote motility of the organism. Furthermore, recent studies demonstrate that mucins modulate the pathogenicity of C. jejuni in a species-specific manner and likely help determine whether these bacteria become pathogenic (as in humans), or adopt a commensal mode of existence (as in chickens and other animals). This review focuses on recent advances in understanding the complex interplay between C. jejuni and components of the mucus layer.